CLINICOPATHOLOGICAL STUDY OF MELANOCYTIC TUMORS OF SKIN - S. SRI GAYATHRI; EZHILVIZHLI ALAVANDAR; KALAIVANI AMIT KUMAR (International Journal of Pharma and Bio Sciences, 2013)
Acquired melanocytic naevi are believed to have been developed from epidermal melanocytes that completed their migration from the neural crest to the dermo-epidermal junction. Uncommon in infancy, naevi increase in frequency during childhood and adolescence and then more slowly to a plateau in middle age. During old age, their prevalence falls. Solar ultraviolet radiation exposure itself has been implicated in both the genesis of new nevi in children and the disappearance of nevi in older adult life. The role of benign melanocytic lesions as precursors and not only as risk markers for the development of cutaneous melanoma is controversial. Nevi are the most important simulants of melanoma, both clinically and histologically, and can usually be reliably distinguished from melanomas. This study is a clinicopathologic analysis of 27 cases of melanocytic tumors